2017
DOI: 10.1089/cbr.2016.2155
|View full text |Cite
|
Sign up to set email alerts
|

213Bi-Labeled Prostate-Specific Membrane Antigen-Targeting Agents Induce DNA Double-Strand Breaks in Prostate Cancer Xenografts

Abstract: Bi-PSMA I&T and Bi-JVZ-008 showed efficient and rapid tumor targeting and produced DSBs in PSMA-expressing LNCaP cells and xenografts. These promising results require further evaluation ofBi-labeled agents with regard to their therapeutic efficacy and toxicity for PCa therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 30 publications
5
41
0
Order By: Relevance
“…We noted that the frequency of α-tracks represents a suitable parameter for biological dose estimation, which is in accordance with recent γ-H2AX studies on DNA damage after internal or external irradiation with α-particles using the γ-H2AX assay 24 , 33 , 34 , 42 . We observed that γ-H2AX was a more robust marker for α-tracks than 53BP1, in agreement with previous observations that γ-H2AX is an indirect DSB marker in the chromatin surrounding DSBs in high LET particle tracks 38 , 43 , 44 .…”
Section: Discussionsupporting
confidence: 90%
“…We noted that the frequency of α-tracks represents a suitable parameter for biological dose estimation, which is in accordance with recent γ-H2AX studies on DNA damage after internal or external irradiation with α-particles using the γ-H2AX assay 24 , 33 , 34 , 42 . We observed that γ-H2AX was a more robust marker for α-tracks than 53BP1, in agreement with previous observations that γ-H2AX is an indirect DSB marker in the chromatin surrounding DSBs in high LET particle tracks 38 , 43 , 44 .…”
Section: Discussionsupporting
confidence: 90%
“…Chatalic et al [100] reported the 111 In-DTPA-labeled engineered expression-modified nanobody JVZ-007, with a myc-tag and cys tag ( 111 In-JVZ007-c-myc-his and 111 InJVZ007-cys), which displayed good PSMA-positive tumor-targeting capability with rapid blood clearance in vivo. The therapeutic usefulness of the PSMA nanobody was evaluated for the first time in 2017 [101]. This study revealed an efficient and rapid prostate tumor-targeting by the JVZ-008 nanobody labeled with 213 Bi ( 213 Bi-JVZ-008) in mice bearing PSMA-positive LNCaP xenograft.…”
Section: Minibodies Diabodies Single-chain Variable Region Fragmentmentioning
confidence: 99%
“…To our knowledge, few accounts of preclinical therapy studies of PSMA-targeting a-radioligand therapeutics have been reported, and none have shown such a profound antitumor effect. 213 Bi-PSMA-I&T was shown to induce double-strand breaks in LNCaP xenograft tumor cells, but tumor uptake was low (5.75 6 2.70 %ID/g at 1 h after injection), tumor-to-kidney ratio poor (0.19 6 0.10), and relatively few a-tracks and double-strand breaks were evident in the tumor 24 h after injection (34). An investigation of 211 At-6 was conducted in mice bearing subcutaneous PC3-PIP tumors with a maximum initial volume of 200 mm 3 (31).…”
Section: Discussionmentioning
confidence: 99%